Time course of hepatitis E‐specific antibodies in adults. Issue 1 (4th October 2016) - Schemmerer, M.; Rauh, C.; Jilg, W.; Wenzel, J. J.
Summary: Hepatitis E virus (HEV) is highly endemic in industrialized countries, but there is a lack of knowledge on individual and overall antibody concentration dynamics. The aim of this study was to characterize longitudinal concentration changes of anti‐HEV immunoglobulin G (anti‐HEV IgG) by enzyme immunoassay (EIA). In total, 199 serum samples collected from 45 subjects over 18 years were analysed. A wide range of anti‐HEV IgG levels was found. Overall, anti‐HEV IgG significantly decreased after an observation period of at least 5 years. One negative seroconversion was observed. Four individual profiles suggested single and even multiple HEV reinfections despite pre‐existing HEV antibodies.